Fluctuation of pain by weather change in musculoskeletal disorders. - Salek, KM; Mamun, MA; Parvin, N; Ahmed, SM; Khan, MM; Rijvi, AN; Rahman, MH; Khasru, MR; Akther, A; Rahman, M; et al. (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2011 Oct;20(4):645-51 The abstract of this article is available on the PubMed website